Phosphorus load base carrying capacity estimation for fish culture in Lake Ranau in Indonesia. Issue 1 (November 2021) - Lukman, L; Dina, R; Ibrahim, A; Waluyo, A
Abstract: Carrying capacity is the ability of waters to accommodate pollutant load inputs without reducing the water quality. For aquaculture in floating net cages (FNC), the carrying capacity is a criterion to achieve the maximum fish production based on the level of total phosphorus (TP) released from the activity, which is still acceptable according to utilisation purposes. Lake Ranau in Sumatra is essential in supporting the socio-economic needs of the people in the surrounding areas, including FNC activities. The development of FNC as an aquaculture model in open waters will have a positive value as long as it is within the limits of water carrying capacity. Thus, the carrying capacity of Lake Ranau waters needs to be estimated to provide optimal direction for FNC development in line with other activities such as tourism. The carrying capacity was estimated using the Beveridge (1987) formulation that has also been adopted into the Ministry Regulation of Environment number 28/2009. As a limiting factor for tourism purposes, the status trophic of waters should be oligotrophic or oligo-mesotrophic. Therefore, the fish production that can be achieved is between 0 tons/year (oligotrophic scale) to 1, 662 tons/year (oligo-mesotrophic scale).